Overview of purple blotch disease and understanding its management through chemical, biological and genetic approaches - Aejaz Ahmad DAR; Susheel SHARMA; Reetika MAHAJAN; Muntazir MUSHTAQ; Ankila SALATHIA; Shahid AHAMAD; Jag Paul SHARMA (Journal of Integrative Agriculture, 2020)
Purple blotch disease of Allium spp. crops caused by Alternaria porri has remained a major concern in agriculture for both farmers and research fraternity as it severely damages the crops and drastically reduces the yield. The symptoms appear after 1–4 days of infection and bulb rot begin, and eventually turn into dark reddish-purple and then brownish/black lesions. Many factors like season, time of sowing, humidity and temperature, stage of crop, and plant architecture have a huge impact on the progression of purple blotch disease. Many genic markers based on amplification of an Alta1 gene sequence have been designed for identification and differentiation of different Alternaria species groups. Among the most commonly used fungicides, mancozeb, tebuconazole, difenaconazole and azoxystrobin were found to be the ideal for the management of purple blotch disease and increased garlic yield. Many biological approaches such as plant extracts and bio-control agents were found partially effective for controlling the disease. A report on QTL mapping for purple blotch resistance discovered that purple blotch resistance is controlled by a single dominant gene ApR1. To completely understand the purple blotch disease resistance for crop improvement, a study is required at transcriptome level for hunting purple blotch resistant genes by gene annotation and mining. Genetic engineering and genome editing are other approaches that can be done for engineering disease resistance in Allium crops for genetic improvement.